An analysis of language error sin final examination papers in Universiti Teknologi MARA / Jun Nirlawati Mohd Sahidol, Kamisah Ariffin and Rahimah Abd Wahab - Mohd Sahidol, Jun Nirlawati; Ariffin, Kamisah; Abd Wahab, Rahimah (2010)
Studies on language errors have been replete, ranging from the analysis on errors in students' written works to errors in public documents such as brochures, articles and advertisements. Studies on errors committed in examination papers have been scarce. Perhaps, this is due to the assumption that examination papers would have gone through a stringent series of editing and proofreading process before they can be approved. However, the occurrence of language related errors such as lexical and syntactical errors in some of the final examination papers in Universiti Teknologi MARA has shown that such assumption is wide off the mark. This has motivated the present study to be carried out as the researchers feel that this problem should be highlighted so that stringent measures can be taken in order to ensure that the papers are free from errors. This study identified and analysed the language errors that occur in the final examination papers. Thus, the data for the study mainly consisted of final examination papers that were randomly selected from the January - April 2008 and July - October 2008 sessions. Altogether, a total of 916 papers were selected from 22 faculties. The data were complemented by the interview data collected from 6 lecturers who had had the experience and had been involved in preparing examination papers.